Pengaruh Pertumbuhan Laba dan Ukuran Perusahaan Terhadap Nilai Perusahaan Indeks LQ45 - Ubaidillah, Adeknya; Meirisa, Faradila (MDP Student Conference, 2025)
The. LQ45 Inde.x is one. of the. major stock indice.s on the. Indone.sia Stock E.xchange.. The. companie.s include.d in this inde.x are. se.le.cte.d base.d on pre.de.te.rmine.d crite.ria. This study aims to e.xamine. the. e.ffe.ct of E.arnings Growth and Firm Size. on Firm Value.. The. data use.d in this re.se.arch come.s from the. financial state.me.nts of LQ45 companie.s for the. pe.riod 2019-2023. The. sampling me.thod use.d in this study is purposive. sampling. The. population of this study consists of 62 companie.s, while. the. sample. include.s 23 companie.s. The. hypothe.sis te.sting in this study use.s multiple. line.ar re.gre.ssion analysis with SPSS 26 software.. The. re.sults of the. partial te.st (t-te.st) indicate. that E.arnings Growth and Firm Size. have. a positive. and significant impact on Firm Value.. Base.d on the. simultane.ous te.st (F-te.st), it shows that the. E.arnings Growth and Firm Size. have. a simultane.ous e.ffe.ct on Firm Value..